Computed Tomographic Scan Evaluation of Pulmonary Blastomycosis - Suzanne Ronald; Jacek Strzelczyk; Sean Moore; Elly Trepman; Mary Cheang; Bill Limerick; Lyle Wiebe; Pete Sarsfield; Kerry MacDonald; Michael Meyers; John M Embil (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Blastomycosis is an uncommon granulomatous pulmonary and extrapulmonary infectious disease caused by the thermally dimorphic fungus Blastomyces dermatitidis. Diagnosis may be delayed or difficult because of varied presentation. The characteristics of blastomycosis on computed tomographic (CT) scan of the chest are not well characterized.